Influence of Additional Income Employees and Discipline on The Performance of Employees of The Regional Forestry Service of North Sulawesi Province - Suan, Semuel Viktor Bai; Mandagi, Marthinus; Bogar, Wilson (Technium Social Sciences Journal, 2022)
To improve professional productivity and growth in the discipline of civil servants, then guidelines are set as a reference for measuring the performance and Discipline of civil servants in the North Sulawesi Provincial Government as part of the consideration of providing additional income for civil servants (North Sulawesi Governor Regulation Number 72 of 2017 concerning Accountability). The type of study used is descriptive research with a quantitative analysis approach where the. The results, especially those obtained from the questionnaire, are processed with statistical data and the percentage of respondents' answer modes in a single table. To collect data in this study, the following techniques were used: The following techniques were used to distribute questions to respondents, who were determined based on the number of samples. The data analysis technique used by the author in this study is a quantitative data analysis technique. In this study, using numbers and drawing conclusions from the research results were analyzed as a presentation through analysis. Based on research conducted on 30 employees of the Forestry Service of North Sulawesi Province, so could conclude that Incentive positively affects employee performance. Based on research conducted on 30 North Sulawesi Provincial Forestry Service employees, it can be concluded that Work Discipline positively affects employee performance. Based on research conducted on 30 employees of the Forestry Service of North Sulawesi Province, it can be concluded that incentives and Discipline work together significantly affect employee performance.